Physicians' perspectives of adopting computer-assisted navigation in orthopedic surgery. (October 2016) - Hsu, Hui-Mei; Chang, I-Chiu; Lai, Ta-Wei
Highlights: Computer-assisted orthopedic surgery (CAOS) has emerged as a new and independent area of musculoskeletal diseases in orthopedics and traumatology. Most of the CAOS related studies focused predominantly on operative skills and reported clinical outcomes of CAOS outperform the manual methods. A CAOS is useless if it is not being used by the physicians. This study used a technology acceptance research model to examine the determinants of continued CAOS use of clinical orthopedists. Suggestions in user management when encountering an obstacle in implementing a CAOS are provided. Abstract: Objectives: Using Computer-assisted orthopedic navigation surgery system (CAOS) has many advantages but is not mandatory to use during an orthopedic surgery. Therefore, opinions obtained from clinical orthopedists with this system are valuable. This paper integrates technology acceptance model and theory of planned behavior to examine the determinants of continued CAOS use to facilitate user management. Methods: Opinions from orthopedists who had used a CAOS for at least two years were collected through a cross-sectional survey to verify the research framework. Follow-up interviews with an expert panel based on their experiences of CAOS were conducted to reason the impacts of factors of the research framework. Results: The results show that factors of "perceived usefulness" and "facilitating condition" determine the intention to continue using CAOS, and "perceived usefulness" was driving by "complexity of task" and "social influence". Additionally, support in practice from high-level managers had an influence on orthopedists' satisfaction after using a CAOS. Conclusions: The aging population is accompanied by the increasing requirements for medical care and medical care attendant expenses, especially in total knee replacement. More precision and improvements on survivorship of patients' artificial joints are needed. This study facilitates suggestions in user management when encountering an obstacle in implementing a CAOS. Based on these findings, scientific and practical implications are then discussed.